Indicators of Changes in Postural Stability with Chronic Nonspecific Neck Pain - Maryam Saadat; Mohammad Jafar Shaterzadeh Yazdi; Ali Asghar Arastoo; Shahla Zahednegad; Hossein Negahban Seuki; Abdol Hossein Bigdeli (Majalah-i ̒ilmī pizishkī-i jundī/shapūr)
Background and Objective: Patients with neck pain are the second largest group after low back pain attended for physical therapy. Sensorimotor deficits in chronic nonspecific neck pain may alter cervical afferent input. Altered sensory input of the cervical spine structure, mediated via the direct neurophysiologic connections to vestibular and visual system has the potential to disturb postural control.Subjects and Methods: In this case-control study, postural stability was measured by force plate in 24 nonspecific chronic neck pain & 24 matched healthy subjects. Each case performed double limb & single limb standing with t level of difficulty (rigid-foam surface). Measured parameter were mean velocity, standard deviation velocity in the media-lateral and anterior-posterior direction. Data were analyzed by 2-way repeated measurement ANOVA.Results: Finding shows that there was a significant increase in standard deviations for velocity in the anterior-posterior and media-lateral direction in single limb stance of subjects with non-specific chronic nonspecific neck pain. In double limb stance, statistically significant differences were found in both allocated groups.Conclusion: Dissimilarity in postural performance chronic nonspecific neck patient is a reflection of different degrees of disturbances of the proprioceptive input to central nervous system and/or of the central processing of such input. Therefore, treatment methods for address neck position and balance training are suggested.